Students' Practices of Scientific Investigation (PoSI) on the Learning of Food Test Materials Using an Explicit Instructional Approach - I Nyoman Sudyana; Asita Al Mufida (Jurnal Penelitian Pendidikan IPA, 2023)
Carrying out assignments through scientific investigations is one of the most meaningful learning experiences for students. In addition, these activities can also have a positive influence on students' interest in learning science. In Indonesia, scientific investigation skills are a skill that students must possess. However, the fact is that there are still many students who have not mastered these skills properly. Therefore, this study aims to look at students' scientific investigation skills through Practices of Scientific Investigation (PoSI) using an explicit instructional approach. This study used the Quasy Experimental Research method, with a pretest-posttest control group design research design. The results obtained indicate that the five skills in PoSI seen in this study have not all been mastered perfectly by students, there are some skills that are still not possessed by students. Overall, the investigative skills (PoSI) of students in the treatment class showed better results when compared to students in the control class. The use of the explicit instructional approach applied in this study helps students carry out the five skills in the PoSI. The five skills in question are skills in making problem formulations, making hypotheses, designing experiments, analyzing experimental results, and making conclusions on experimental results. Habit is needed in developing some of the skills in the PoSI in students.